ففتھ جنریشن وار کا دفاع قرآن و سنت کی روشنی میں: The Defense of Fifth Generation Warfare in the Light of the Quran and Sunnah - Attique, Muhammad; Ahmad , Manzoor (FIKR-O NAZAR فکر ونظر, 2024)
: Fifth Generation Warfare (5GW), characterized by information manipulation, cyberattacks, and social engineering, presents a complex challenge in the contemporary world. This paper explores the permissibility and ethical considerations of employing 5GW tactics from an Islamic perspective. Drawing upon the Quran and Sunnah, the paper examines the core principles of self-defense and protection of the Muslim community. It analyzes verses advocating for strategic action against aggressors and the Prophet's (ﷺ) use of tactics that could be interpreted as precursors to 5GW methods. However, the paper acknowledges the potential for manipulation and civilian harm within 5GW. It delves into Quranic verses and hadiths emphasizing justice, truthfulness, and the avoidance of innocent bloodshed. The paper proposes a framework for ethical 5GW conduct, emphasizing targeted operations, minimizing civilian casualties, and adhering to international law where applicable. This analysis aims to contribute to a nuanced discussion on 5GW in the Islamic context. It argues that while 5GW tactics can be permissible for self-defense under certain conditions, they must be employed with strict adherence to Islamic ethical principles.